Novel chitosan-quinic acid nanoparticles labeled with m99 technetium for breast cancer imaging - Atousa Zia; Hakimeh Rezaei Aghdam; Mostafa Saffari; Jafar Farzaneh; Morteza Pirali Hamedani; Seyed Esmaeil Sadat Ebrahimi; Kimia Abdollahi; Saghar Sedigh Kheirabad; Fatemeh Zarringhalam; Farnoor Davachi omoomi; Ramin Farhoudi; Mehdi Shafiee Ardestani (Nanomedicine Journal, 2022)
Objective(s): Today, cancer is one of the health concerns in modern societies. The use of nanoparticles in medical science has created new possibilities for diagnosis, imaging of tumors, and treatment of cancer in humans. Materials and Methods: In this study, chitosan nanoparticles modified with quinic acid were used to diagnose breast cancer using a single-photon emission computed tomography imaging technique. For this purpose, quinic acid was activated by EDC/NHS and then binding was performed by adding chitosan nanoparticles. Results: TEM, DLS, FTIR, and LC/MASS analyzes were used to investigate this conjugation. MTT toxicity test showed no toxicity on the HEK-293 cell lines and therapeutic properties for the MCF-7 cell line. The response surface method depends on the central composite design that was applied. For the highest labeling efficiency, using 3 factors: the amount of chitosan-quinic acid, pH, and SnCl2 as a reducing agent, and the efficiency of labeling was evaluated by thin-layer chromatography (TLC). Conclusion: Finally, the study of biodistribution using SPECT imaging in cancer mice and its comparison with blocking tests showed that this compound has a good ability to diagnose breast cancer.